Human Resource Management in Islamic Junior High School of Insan Qurani - Yasir, Muhammad; Yusrizal, Yusrizal; Niswanto, Niswanto (Jurnal Pendidikan Progresif, 2021)
The purpose of this research was to find out human resource management, especially of the teachers in the Insan Qurani Islamic Private Junior High School. It consists of planning systems, recruitment systems, evaluation systems, training and development system. A descriptive method with a qualitative approach was used in this research. The data were collected through interviews, observation, and documentation. The principal and the teachers were the subjects of this research. The results of the research indicate that: (1) planning had been formed by analyzing the volume of the workload and then determining the number of teachers needed, (2) recruitment was done by understanding the needs, selecting the applicants, interviewing them, and making a decision, (3) a well-planned evaluation was carried out regularly through an identification of the documents related to the performance of the teachers, an examination of the completeness of the learning tools, and a direct observation of the teaching and learning process in each classroom, (4) training and development was planned regularly through workshops, training programs, seminars, and other activities related to education. Keywords: management, human resource, junior high school DOI: 10.23960/jpp.v11.i2.202124